A double-layer cellulose fiber hydrogel and preparation method thereof
By adopting a bilayer structure of cellulose fiber hydrogel, the problem of single-layer cellulose fiber hydrogel prone to break under stress is solved by combining cellulose fibers with hydrogel matrix, the problem of single-layer cellulose fiber hydrogel is solved, significantly improving the fracture toughness and biocompatibility of the material, and enhancing its application potential in tissue repair and environmental protection.
Patent Information
- Application Number
- CN202411009140.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-07-25
AI Technical Summary
Single-layer cellulose fiber hydrogels are prone to fracture when subjected to tensile or compressive stresses, limiting their application in complex tissue repair.
Using the preparation method of a double-layer cellulose fiber hydrogel, a double-layer structure is formed by adding a polymerization precursor solution to the upper and lower layers of the cellulose fiber hydrogel, and a photocuring treatment is used. This structure enhances the overall performance of the material through the composite of cellulose fibers and hydrogel matrix.
The double-layer cellulose fiber hydrogel significantly enhances the fracture toughness of the hydrogel, imparts good biocompatibility, strong interface bonding strength and water retention, and improves its application value in the fields of biomedical and environmental protection.
Smart Images

Figure CN118955949B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymers and preparation methods thereof, and particularly relates to a double-layer cellulose fiber hydrogel and a preparation method thereof. Background Art
[0002] In the field of biomaterials science, the pursuit of more efficient and natural methods of human tissue repair has always been a hot topic of research. Tissue repair technology is particularly important when dealing with trauma, disease or congenital defects, but traditional methods have problems such as slow healing, scar formation and limited donor tissue. Therefore, it is particularly important to develop new biomaterials to simulate and replace the structure and function of damaged tissues. Ideal tissue repair materials should not only simulate the mechanical properties of natural tissues, but also have good biocompatibility and bioactivity to promote cell growth, differentiation and tissue regeneration. In recent years, cellulose fiber hydrogels have received widespread attention in the field of tissue repair due to their unique physicochemical properties, such as good biocompatibility, high water absorption and adjustable mechanical properties. As a hydrophilic three-dimensional network structure soft material, hydrogels are widely used in drug delivery, tissue repair, wound dressings and other fields due to their similar chemical and mechanical properties to biological tissues. As biological scaffold materials, they help damaged tissues regenerate and recover. However, these fields have extremely high requirements for the mechanical durability of the materials, especially in soft robots and wearable devices. The materials need to withstand complex deformations such as repeated stretching and bending, which places higher requirements on the hydrogel's resistance to fracture.
[0003] To enhance the mechanical durability of hydrogels, researchers have explored a variety of methods, including adding nanomaterials and changing the structural design. The introduction of nanomaterials can enhance the mechanical properties and stability of hydrogels, while the optimization of structural design can improve the overall performance of hydrogels. Cellulose fiber hydrogels not only have a network structure similar to the natural extracellular matrix, providing an ideal microenvironment for cell adhesion, proliferation and differentiation, but also their high water absorption and water retention also provide the necessary moisture support for tissue repair. However, cellulose fiber hydrogels with a single structure often have deficiencies in mechanical properties, especially when subjected to tensile or compressive stress, they are prone to breakage, which limits their application in complex tissue repair. Summary of the invention
[0004] The purpose of the present invention is to provide a double-layer cellulose fiber hydrogel and a preparation method thereof, which not only enhances the overall performance of the material but also gives the material good biocompatibility, strong interface bonding strength and water retention through the composite of cellulose fibers and hydrogel matrix in the double-layer structure.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a double-layer cellulose fiber hydrogel comprises the following steps:
[0007] S1. Dissolve the dried microcrystalline cellulose in urea solution, stir evenly, and let stand overnight;
[0008] S2, adding LiOH to the solution in step S1, stirring evenly, and then adding a chemical crosslinking agent, stirring evenly to obtain a cellulose solution;
[0009] S3, pouring a mixed liquid of cellulose solution and polymer precursor solution into a 1 mm high mold, performing a light curing treatment, and then cutting a 20 mm long pre-crack at the center of the cured product to obtain an upper layer of cellulose fiber hydrogel;
[0010] S4. Pour a mixed liquid of cellulose solution and polymer precursor solution into a 2 mm high mold, spread the upper layer of cellulose fiber hydrogel prepared in step S3 on the mixed solution in the mold, and perform photocuring to obtain a double-layer cellulose fiber hydrogel.
[0011] Preferably, the drying conditions of the microcrystalline cellulose in step S1 are 50-70° C. and the drying time is 18-30 hours.
[0012] Further preferably, the drying condition of the microcrystalline cellulose in step S1 is 60° C. and the drying time is 24 h.
[0013] Preferably, in step S1, the dried microcrystalline cellulose is dissolved in a urea solution, stirred at 200-500 rpm for 2-5 hours, and then placed in an environment of -15--30°C overnight.
[0014] Preferably, in step S1, the dried microcrystalline cellulose is dissolved in a urea solution, stirred at 300 rpm for 4 hours, and then placed in a -20°C environment overnight.
[0015] Preferably, after adding LiOH in step S2, stirring is performed at 200-500 rpm for 30-60 min, and then a chemical crosslinking agent is added, and stirring is performed at 200-500 rpm for 30-60 min to obtain a cellulose solution.
[0016] Further preferably, after adding in step S2, stirring is performed at 300 rpm for 30 min, and then a chemical cross-linking agent is added and stirred at 300 rpm for 30 min to obtain a cellulose solution.
[0017] Preferably, the chemical cross-linking agent in step S2 is epichlorohydrin.
[0018] Preferably, the polymerization precursor solution in step S3 includes one or more of acrylamide, deionized water, a crosslinking agent and a photoinitiator.
[0019] More preferably, the crosslinking agent is N,N'-methylenebisacrylamide; and the photoinitiator is phenyl (2,4,6-trimethylbenzoyl) lithium phosphate.
[0020] Preferably, the light curing reaction conditions in step S3 are: the power of the ultraviolet lamp is set to 25-50W, the wavelength is 365nm, and the light intensity is 1.5mW / cm 2 , the reaction time is 30-60min.
[0021] Further preferably, the photopolymerization reaction conditions in step S3 are: power 30W, wavelength 365nm, light intensity 1.5mW / cm 2 , reaction time 30min.
[0022] Preferably, the photocuring reaction conditions in step S4 are: the UV lamp power is set to 25-50W, the wavelength is 365nm, and the light intensity is 1.5mW / cm 2 , the reaction time is 30-60min.
[0023] Further preferably, the photopolymerization reaction conditions in step S4 are: power 30W, wavelength 365nm, light intensity 1.5mW / cm 2 , reaction time 30min.
[0024] The invention also provides a double-layer cellulose fiber hydrogel prepared by the preparation method.
[0025] Compared with the prior art, the present invention has the following advantages and technical effects:
[0026] 1. The present invention provides a double-layer cellulose fiber hydrogel and a preparation method thereof. The interface of the double-layer structure can effectively shield cracks and change the crack propagation path, thereby significantly enhancing the fracture toughness of the hydrogel. At the same time, the composite of cellulose fibers and hydrogel matrix in the double-layer structure gives the material good biocompatibility, strong interface bonding strength and water retention.
[0027] 2. The double-layer cellulose fiber hydrogel with high fracture toughness has potential application value in the biomedical field and can be used as a scaffold material for tissue engineering, which can withstand more biomechanical effects without breaking, thereby improving the success rate of treatment and the service life of the material. In terms of environmental protection, the high fracture toughness of the double-layer cellulose fiber hydrogel provided by the present invention makes it an ideal filter material or adsorbent, which can cope with complex and harsh environmental conditions and improve filtration efficiency and adsorption performance.
[0028] 3. The preparation process of the present invention is simple, has low preparation process cost and high safety, and is suitable for industrial mass production.
[0029] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the dissolution process of cellulose of the present invention;
[0031] Figure 2 The stress-stretch curves of the single-layer cellulose fiber hydrogels provided in Examples 1-7;
[0032] Figure 3 Statistical graph of elastic modulus of single-layer cellulose fiber hydrogel provided in Examples 1-7;
[0033] Figure 4 Flow chart for the preparation of double-layer cellulose fiber hydrogel;
[0034] Figure 5 Optical microscope images of the hydrogels provided in Example 8 and Comparative Example 1, wherein: Figure 5 (a) is an optical microscope image of a double-layer cellulose fiber hydrogel provided in Example 8, Figure 5 (b) is an optical microscope image of the cellulose-based hydrogel provided in Comparative Example 1;
[0035] Figure 6 The SEM images of the double-layer cellulose fiber hydrogel provided in Example 8 at different scales, wherein: Figure 6 (a) is a SEM image with a scale of 200 μm. Figure 6 (b) is a SEM image with a scale of 50 μm. Figure 6 (c) is a SEM image with a scale of 20 μm. Figure 6 (d) is the SEM image with a scale of 2 μm;
[0036] Figure 7 Stress-stretch curves of the double-layer cellulose fiber hydrogels provided in Examples 8-13;
[0037] Figure 8 This is a schematic diagram of the adhesion results of the double-layer cellulose fiber hydrogel provided in Example 8;
[0038] Fig. 9 A schematic diagram of a uniaxial stretching experiment of a double-layer cellulose fiber hydrogel provided in Example 8;
[0039] Fig.10 The performance test results of the cellulose fiber hydrogel provided in Examples 1-7 and Examples 8-13, wherein: Fig.10 (a) is a statistical graph of the fracture toughness results of the single-layer cellulose fiber hydrogel provided in Examples 1-7, Fig.10(b) is a statistical graph of the fracture toughness results of the double-layer cellulose fiber hydrogel provided in Examples 8-13, Fig.10 (c) is a statistical diagram of the critical tensile value of the single-layer cellulose fiber hydrogel provided in Examples 1-7, Fig.10 (d) is a statistical graph of the critical tensile value results of the double-layer cellulose fiber hydrogel provided in Examples 8-13;
[0040] Fig.11 Schematic diagram of pure shear of cellulose fiber hydrogel provided in Example 1 and Example 8, wherein Fig.11 (a) is a pure shear schematic diagram of a single-layer cellulose fiber hydrogel provided in Example 1, Fig.11 (b) is a pure shear schematic diagram of the double-layer cellulose fiber hydrogel provided in Example 8;
[0041] Fig.12 The energy release rate statistics of the cellulose fiber hydrogels provided in Examples 1-7 and Examples 8-13, wherein: Fig.12 (a) is a statistical diagram of a single-layer cellulose fiber hydrogel provided in Examples 1-7, Fig.12 (b) is a statistical diagram of the double-layer cellulose fiber hydrogel provided in Examples 8-13;
[0042] Fig.13 The double-layer cellulose fiber hydrogel peeling test results provided in Examples 8-13, wherein: Fig.13 (a) is the load-displacement diagram. Fig.13 (b) is a schematic diagram of the double-layer cellulose fiber hydrogel peeling test process. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0044] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0045] Sources of experimental materials used in the present invention: acrylamide (AAM), N,N-methylenebisacrylamide (MBAA), and microcrystalline cellulose (MCC) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. The particle size of microcrystalline cellulose is about 147 μm. Phenyl (2,4,6-trimethylbenzoyl), lithium hydroxide (LiOH), and urea were purchased from Beijing Honghu United Chemical Products Co., Ltd. All reagents in this experiment were used directly without further purification. Unless otherwise specified, other raw materials are conventional commercial products in the field.
[0046] Example 1 This example provides a method for preparing a single-layer cellulose fiber hydrogel, comprising the following steps:
[0047] S1, dissolving 4 g of microcrystalline cellulose dried at 60° C. for 24 h in a urea solution, wherein the urea solution is prepared by dissolving 15 g of urea in 80.4 g of deionized water, stirring at 300 rpm for 4 h, and then placing the mixture in a -20° C. environment overnight;
[0048] S2, adding 4.6 g of LiOH to the solution in step S1, stirring at 300 rpm for 30 min, then adding 2 g of epichlorohydrin, stirring at 300 rpm for 30 min, to obtain a cellulose solution;
[0049] S3. A mixed liquid of cellulose solution and polymerization precursor solution in equal proportions was poured into a 1 mm high mold, wherein the amounts of acrylamide, N,N'-methylenebisacrylamide and phenyl (2,4,6-trimethylbenzoyl) phosphate lithium salt added to the polymerization precursor solution were 24 g, 0.1 g and 0.12 g respectively. The mixture was illuminated by ultraviolet light at a power of 30 W, a wavelength of 365 nm and an illumination intensity of 1.5 mW / cm 2 The photocuring reaction was initiated under the conditions and the reaction lasted for 30 minutes to obtain a single-layer cellulose fiber hydrogel.
[0050] The preparation method of Example 2 is the same as that of Example 1, except that the amount of acrylamide added is 26 g.
[0051] The preparation method of Example 3 is the same as that of Example 1, except that the amount of acrylamide added is 28 g.
[0052] The preparation method of Example 4 is the same as that of Example 1, except that the amount of acrylamide added is 32 g.
[0053] The preparation method of Example 5 is the same as that of Example 1, except that the amount of acrylamide added is 34 g.
[0054] The preparation method of Example 6 is the same as that of Example 1, except that the amount of acrylamide added is 36 g.
[0055] The preparation method of Example 7 is the same as that of Example 1, except that the amount of acrylamide added is 40 g.
[0056] Example 8 This example provides a double-layer cellulose fiber hydrogel.
[0057] S1, dissolving 4 g of microcrystalline cellulose dried at 60° C. for 24 h in a urea solution, wherein the urea solution is prepared by dissolving 15 g of urea in 80.4 g of deionized water, stirring at 300 rpm for 4 h, and then placing the mixture in a -20° C. environment overnight;
[0058] S2, adding 4.6 g of LiOH to the solution in step S1, stirring at 300 rpm for 30 min, then adding 2 g of epichlorohydrin, stirring at 300 rpm for 30 min, to obtain a cellulose solution;
[0059] S3. Pour a liquid mixed with a cellulose solution and a polymerization precursor solution in equal proportions into a 1 mm high mold, wherein the amounts of acrylamide, N,N'-methylenebisacrylamide and phenyl (2,4,6-trimethylbenzoyl) lithium phosphate added to the polymerization precursor solution are 24 g, 0.1 g and 0.12 g respectively. Use ultraviolet light at a power of 30 W, a wavelength of 365 nm and an illumination intensity of 1.5 mW / cm 2 The photocuring reaction was initiated under the conditions and the reaction lasted for 30 min. Then, a 20 mm long pre-crack was cut at the center of the cured product to obtain the upper layer of cellulose fiber hydrogel.
[0060] S4, pouring a liquid mixed with cellulose solution and polymerization precursor solution in equal proportion into a 2 mm high mold, wherein the amount of acrylamide, N,N'-methylenebisacrylamide and phenyl (2,4,6-trimethylbenzoyl) phosphate lithium salt added to the polymerization precursor solution is 26g, 0.1g and 0.12g respectively, and the upper layer of cellulose fiber hydrogel prepared in step S3 is spread flat on the mixed solution in the mold, and ultraviolet light is used at a power of 30W, a wavelength of 365nm, and a light intensity of 1.5mW / cm 2 The photocuring reaction was initiated under the conditions and the reaction lasted for 30 minutes to obtain a double-layer cellulose fiber hydrogel.
[0061] The preparation method of Example 9 is the same as that of Example 8, except that the amount of acrylamide added in step S4 is 28 g, and a double-layer cellulose fiber hydrogel is obtained.
[0062] Example 10
[0063] The preparation method is the same as that of Example 8, except that the amount of acrylamide added in step S4 is 32 g, and a double-layer cellulose fiber hydrogel is obtained.
[0064] Embodiment 11
[0065] The preparation method is the same as that of Example 8, except that the amount of acrylamide added in step S4 is 34 g, and a double-layer cellulose fiber hydrogel is obtained.
[0066] Example 12
[0067] The preparation method is the same as that of Example 8, except that the amount of acrylamide added in step S4 is 36 g, and a double-layer cellulose fiber hydrogel is obtained.
[0068] Embodiment 13
[0069] The preparation method is the same as that of Example 8, except that the amount of acrylamide added in step S4 is 40 g, and a double-layer cellulose fiber hydrogel is obtained.
[0070] Comparative Example 1 This comparative example provides a cellulose-based hydrogel,
[0071] S1, dissolving 4 g of microcrystalline cellulose dried at 60° C. for 24 h in a urea solution, wherein the urea solution is prepared by dissolving 15 g of urea in 80.4 g of deionized water, stirring at 300 rpm for 4 h, and then placing the mixture in a -20° C. environment overnight;
[0072] S2, adding 4.6 g of LiOH to the solution in step S1, stirring at 300 rpm for 30 min, then adding 2 g of epichlorohydrin, stirring at 300 rpm for 30 min, to obtain a cellulose solution;
[0073] S3, adding cellulose solution to acrylamide hydrogel in equal proportions, wherein the amount of acrylamide added is 24 g, and ultraviolet light is used at a power of 30 W, a wavelength of 365 nm, and an illumination intensity of 1.5 mW / cm 2 The photocuring reaction was initiated under the conditions and the reaction lasted for 30 minutes to obtain a cellulose-based hydrogel.
[0074] The effects of the hydrogels provided in the above embodiments were verified by the following experiments:
[0075] 1. Scanning electron microscope test:
[0076] Apply conductive carbon glue on the sample stage, pick up the sample with tweezers and stick it on the conductive carbon glue. After the sample stage with the sample is put into liquid nitrogen slush for quick freezing for 30 seconds, it is transferred to the sample preparation chamber under vacuum state using a low-temperature freezing preparation transfer system for sublimation gold plating. After the sample is sublimated at -90℃ for 10 minutes, it is sputter-plated with gold at a current of 10mA for 60 seconds. Finally, the processed samples are observed and analyzed at the microscopic level by scanning electron microscopy (Hitachi SU8010, PP3000T, Japan).
[0077] 2. Mechanical testing:
[0078] All mechanical tests were performed at room temperature using an IBTC-300 micro in-situ mechanical testing machine with a 20N sensor. Pure shear (PS) tests were performed to measure the fracture properties of the hydrogels. The pure shear test was originally proposed by Rivlin and Thomas to test the fracture of rubber samples and has recently been used to characterize gel fracture. Uncracked and cracked samples were used. The size of the uncracked hydrogel was 50mm×50mm×1mm. After being glued between two clamps, the uniaxial tensile test was performed. The sample size was 50mm×10mm×1mm (H=10mm). The cracked sample was prepared by introducing a c=20mm crack in the middle of the sample by a blade. The tensile λ is defined as the current length divided by the initial length of the specimen. The nominal stress is defined as the applied force divided by the cross-sectional area of the specimen in the undeformed state.
[0079] To measure fracture toughness, we stretched cracked and uncracked specimens at a rate of 50 mm / min. Fracture toughness is calculated as Γ = HW(λc), where H is the height of the sample and W(λc) is the integral of the stress-stretch curve of the crack-free sample from λ = 1 to the critical stretch λ = λc, where λc is defined as the stretch at which crack growth begins. The energy release rate is calculated as G = HW(λ s ), λ s Defined as the stretch before crack growth begins.
[0080] In order to measure the elastic modulus, the crack-free sample was stretched at a speed of 50 mm / min, and the slope of the stress-stretch curve at small deformation was the elastic modulus E.
[0081] In order to verify the fracture resistance of the double-layer cellulose fiber hydrogel, a pure shear test was performed on the double-layer structure.
[0082] The test results are as follows:
[0083] 1. Mechanical properties test results of single-layer cellulose fiber hydrogel:
[0084] Depend on Figure 2 It can be seen that, with the increase of the acrylamide monomer content in Examples 1-7, the single-layer cellulose fiber hydrogel has better toughness and elasticity, can withstand greater tensile and compressive forces, and improves the strength and elongation of the single-layer cellulose fiber hydrogel.
[0085] Depend on Figure 3 It can be seen that when the acrylamide content in Examples 1-7 increases from 24 g to 40 g, the elastic modulus of the cellulose fiber hydrogel film increases significantly.
[0086] 2. Double-layer cellulose fiber hydrogel microstructure results:
[0087] Depend on Figure 5It can be seen that compared with the cellulose-based hydrogel provided in Comparative Example 1, the cellulose in the double-layer cellulose fiber hydrogel provided in Example 8 is completely dissolved.
[0088] Depend on Figure 6 It can be seen that the scanning electron microscope (SEM) images of the double-layer cellulose fiber hydrogel provided in Example 8 at different scales show its unique three-dimensional network structure. This structure is formed by the cellulose fibers interweaving and connecting with each other, forming a complex, porous, sponge-like network.
[0089] 3. Double-layer cellulose fiber hydrogel performance test results:
[0090] Depend on Figure 7 It can be seen that for the double-layer cellulose fiber hydrogels provided in Examples 8-13, as the concentration of the base monomer increases, the length of the polymer chains in the hydrogel becomes longer, the chains are more easily entangled, and the elastic modulus increases accordingly, thus bringing the upper cellulose fiber hydrogel film to a larger critical stretch value λ. Figure 8 It can be seen that the interface in the double-layer structure can effectively disperse and absorb the stress generated at the crack tip due to its interface bonding strength. This dispersion and absorption effect can reduce stress concentration and thus limit the expansion of the crack.
[0091] Depend on Fig. 9 It can be seen that with the increase of tensile force, the double-layer structure of the double-layer cellulose fiber hydrogel provided in Example 8 shows obvious elastic deformation. This deformation characteristic enables the double-layer structure to have a certain buffering effect when subjected to external force.
[0092] In order to further verify the fracture resistance of the double-layer cellulose fiber hydrogels provided in Examples 8-13 and the single-layer cellulose fiber hydrogels provided in Examples 1-7, a crack extension test was conducted, and a pre-crack was introduced between the cellulose fiber hydrogels provided in Examples 1-7 and Examples 8-13. Figure 10-13 .
[0093] Depend on Fig.10 As shown in (a), when the elastic modulus of the single-layer cellulose fiber hydrogel provided in Examples 1-7 increases, its fracture toughness also increases. This shows that the elastic modulus is one of the important factors affecting the fracture toughness of the hydrogel. Fig.10 As shown in (b), the fracture toughness of the double-layer cellulose fiber hydrogel provided by Examples 8-13 also increases with the increase of the elastic modulus of the substrate. This further confirms the important influence of the elastic modulus on the fracture toughness of the cellulose fiber hydrogel. Fig.10As shown in (c) and (d), with the increase of elastic modulus, the critical tensile value of single layer and double layer will increase accordingly. This indicates that the increase of elastic modulus helps to improve the tensile properties of cellulose fiber hydrogel, thereby improving its fracture toughness.
[0094] Depend on Fig.11 As shown in (a) and (b), the high bonding strength of the double-layer structure interface effectively limits the expansion of the crack, allowing the stress to be more evenly distributed between the two layers, reducing stress concentration. When the crack attempts to penetrate the hydrogel, the double-layer structure will change the direction of the crack, effectively shielding the further expansion of the crack through the strong interface bonding strength, thereby slowing down the speed of crack expansion and achieving a toughening effect.
[0095] Depend on Fig.12 As can be seen from (a) and (b) in Figure 2, the normalized energy release rate increases with the increase of applied tension. For the single-layer structure, the normalized energy release rate decreases with the increase of the elastic modulus of the cellulose fiber hydrogel film. This means that the harder the hydrogel film is, the stronger the driving force G for crack propagation. m / E f The lower the c. For the double-layer structure, when the elastic modulus of the substrate increases, the normalized energy release rate also decreases. The harder the substrate, the greater the driving force G for the crack propagation of the substrate-supported hydrogel film. b / E f h f The lower the normalized energy release rate, the higher the fracture toughness of the double-layer cellulose fiber hydrogel. According to the critical fracture condition G = Г, when the material is given (i.e. the fracture toughness Г is fixed), reducing the energy release rate G under a given load or deformation is a way to improve the fracture resistance of the material. Therefore, the lower the normalized energy release rate, the higher its fracture toughness, confirming that the elastic modulus is one of the key factors affecting the fracture toughness of cellulose fiber hydrogel.
[0096] To further explore the interfacial adhesion of the double-layer cellulose fiber hydrogel, a 90° peel test was performed. The double-layer cellulose fiber hydrogel provided in Examples 8-13 was cut into a size of 50 mm (length L) × 15 mm (width W) × 2 mm (thickness T) as the sample to be tested. The upper and lower surfaces of the double-layer structure of the sample to be tested were treated with stickers for subsequent peeling tests. Before the test, the lower layer of paper was first glued to the glass sheet to ensure that it was firmly fixed. Use a testing machine to peel off the upper layer of paper at a certain speed (v = 50 mm / min) to obtain the adhesion of the interface of the double-layer cellulose fiber hydrogel. In order to observe the peeling process more clearly, we painted the part of the hydrogel adhered to the paper red to distinguish it from the color of the paper.
[0097] Depend on Fig.13As shown in (a), the change of hydrogel monomer content has a certain influence on the peeling force between the double-layer cellulose fiber hydrogels.
[0098] Based on the peeling force experiment, the adhesion energy between the double-layer cellulose fiber hydrogel was calculated. Adhesion energy is an important parameter to measure the adhesion performance between materials. Its calculation formula is: Adhesion energy = F / w, where F is the peeling force recorded by the test machine and w is the width of the double-layer cellulose fiber hydrogel sample. The calculated adhesion energy between the double-layer cellulose fiber hydrogel is 33.33 J / m 2 、58J / m 2 、63.33J / m 2 、78.67J / m 2 , 93.33J / m 2 , 106.67J / m 2 This value indicates that the double-layer cellulose fiber hydrogel has high adhesion and can play a good role in various practical applications.
[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a double-layer cellulose fiber hydrogel, characterized in that: The steps include: S1. Dissolve the dried microcrystalline cellulose in urea solution, stir evenly, and let stand overnight; S2, adding LiOH to the solution in step S1, stirring evenly, and then adding a chemical crosslinking agent, stirring evenly to obtain a cellulose solution; S3, pouring a mixed liquid of cellulose solution and polymer precursor solution into a 1 mm high mold, performing a light curing treatment, and then cutting a 20 mm long pre-crack at the center of the cured product to obtain an upper layer of cellulose fiber hydrogel; S4, pouring a mixed liquid of the cellulose solution and the polymer precursor solution into a 2 mm high mold, spreading the upper layer of cellulose fiber hydrogel prepared in step S3 on the mixed solution in the mold, and performing photocuring treatment to obtain a double-layer cellulose fiber hydrogel; In step S2, the chemical cross-linking agent is epichlorohydrin; The polymerization precursor solution in step S3 includes acrylamide, deionized water, a crosslinking agent and a photoinitiator.
2. The preparation method according to claim 1, characterized in that: In step S1, the drying conditions of the microcrystalline cellulose are 50-70° C. and the drying time is 18-30 h.
3. The preparation method according to claim 1, characterized in that: In step S1, the dried microcrystalline cellulose is dissolved in a urea solution, stirred at 200-500 rpm for 2-5 hours, and then placed in a -15- -30°C environment overnight.
4. The preparation method according to claim 1, characterized in that: After adding LiOH in step S2, stirring is performed at 200-500 rpm for 30-60 min, and then a chemical crosslinking agent is added, and stirring is performed at 200-500 rpm for 30-60 min to obtain a cellulose solution.
5. The preparation method according to claim 1, characterized in that: The light curing reaction conditions in step S3 are: the power of the UV lamp is set to 25-50W, the wavelength is 365nm, and the light intensity is 1.5mW / cm 2 , the reaction time is 30-60min.
6. The preparation method according to claim 1, characterized in that: The light curing reaction conditions in step S4 are: the power of the UV lamp is set to 25-50W, the wavelength is 365nm, and the light intensity is 1.5mW / cm 2 , the reaction time is 30-60min.
7. The double-layer cellulose fiber hydrogel prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation method of high-toughness and low-swelling cellulose-based magnetic double-network hydrogel
CN112142993A
Thermosensitive single-layer hydrogel with controllable transparency, preparation method and assembled double-layer hydrogel
CN114891241A
Fiber membrane-hydrogel difunctional composite medical patch and preparation method thereof
CN118304481A